La Interseccionalidad como Instrumento Analítico de Interpelación en la Violencia de Género (Intersectionality, a Methodological Tool for Analysing and Addressing Gender-based Violence) - Raquel Guzman Ordaz; María Luisa Jiménez Rodrigo (Oñati Socio-Legal Series)
This paper reviews peripheral feminism reflections upon the need to move beyond classic gender violence studies’ epistemological assumptions. Gender-based-analysis (GBA) conceptualization represented a considerable advance in recognising patriarchy as a structural system of domination and its relevance in studying processes of violence against women. Nonetheless this approach exhibit limitations as we try to investigate further beyond simple analytical dichotomies so often deployed when discussing gender violence. Consequently we highlight the importance of relating gender to other Intersectional inequality axis such as social class, age, sexual identities different from the heteronormativity, functional diversity, ethnic group/race, or citizenship. An encompassing analytical perspective allows for a multidimensional framework more suitable for the study of such a complex phenomenon as is violence against women. In this manner we are able to visualize and analyse experiences that are usually marginalised and excluded from hegemonic definitions of gender violence.